THE PERCEPTION OF CONSUMERS ON MUSLIM FASHION BRAND IN INDONESIA - Bintang Ika Purwanti; Hendri Hermawan Adinugraha (Tasharruf: Journal Economics and Business of Islam, 2021)
Muslim clothing is the way Muslim women wear their clothes according to Islamic law, namely clothing that is not tight (shaping the curves of the body) and the user of the clothing is a Muslim woman who is obedient to the teachings of her religion in dress procedures. Currently, Muslim clothing is a concern among the clothing industry in Indonesia. In its development, the brand of Muslim clothing has also become one of the consumer's assessments or perceptions of a product. A good brand is one of the assets for the company because the brand has an impact on every consumer perception, where the public will have a positive impression of the product and the company. The purpose of this study is to describe how Indonesian consumers perceive Muslim fashion brands. The type of research used is qualitative research using library research methods. Sources of data used in this study are primary and secondary data sources. While the data analysis technique used in this research is content analysis. The results of this study indicate that brands are extrinsic stimuli that affect consumer perceptions of a product.